Total synthesis and absolute configuration determination of Ktedonoketone, a benzenoid metabolite from Thermophilic bacterium - Dandawate, Monica; Choudhury, Rahul; Krishna, Gamidi Rama; Reddy, D. Srinivasa (Tetrahedron Letters, 2020)
The successful total synthesis of both enantiomers of ktedonoketone allowed us to decipher an unambiguous assignment of absolute configuration of the natural product. The concise synthesis highlights Wacker oxidation and aldol condensation as key steps. In addition to this, the current synthetic route is suitable to access a library of compounds on the similar skeleton as one can use readily available amino acids and Grignard reagents as variants. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Absolute configuration; Ktedonoketone; Total synthesis; Wacker oxidation

Separation of a diastereomeric diol pair using the mechanical properties of crystals - Gamidi, Rama Krishna; Dandawate, Monica; Choudhury, Rahul; Tothadi, Srinu; Nangia, Ashwini; Reddy, D. Srinivasa (Crystengcomm, 2021)
We report the separation of a (2S,3R/S)-3-ethyl-1-phenylhex-5-ene-2,3-diol (ephd) diastereomeric pair with visually indistinguishable acicular morphologies based on their mechanical responses, which is found to be more efficient than conventional separation methods. Furthermore, the molecular crystals of (2S,3R)-ephd show elastic deformation, while (2S,3S)-ephd fractures in a brittle manner under similar conditions.

Total synthesis and absolute configuration determination of the α-glycosidase inhibitor (3S,4R)-6-Acetyl-3-hydroxy-2,2-dimethylchroman-4-yl (Z)-2-Methylbut-2-enoate from Ageratina grandifolia - Dandawate, Monica; Choudhury, Rahul; Krishna, Gamidi Rama; Reddy, D. Srinivasa (Journal of Natural Products, 2023)
Herein, we report the first total synthesis of & alpha;-glycosidaseinhibitor (3R, 4S)-6-acetyl-3-hydroxy-2,2-dimethylchroman-4-yl(Z)-2-methylbut-2-enoate as well as its enantiomer.Our synthesis confirms the chromane structure separately proposedby Navarro-Vazquez and Mata, on the basis of DFT computations. Furthermore,our synthesis allowed us to determine the absolute configuration ofthe natural compound as (3S, 4R)and not (3R, 4S).